2019
DOI: 10.2298/tsci170504188k
|View full text |Cite
|
Sign up to set email alerts
|

Experimental optimization of energy consumption for direct current refrigerator by PID controller tuning and comparison with ON/OFF refrigerator

Abstract: In this research the optimization of energy consumption for DC refrigerator used in commercial cold store was conducted. To achieve this object a test facility was installed into the introduction room of a national refrigeration company. Due to the imperfect data given by the producer, the proportional-integral-derivative controller of DC refrigerator had to be tuned by setting the correct proportional, integral and derivative parameter values to achieve optimal energetic operation. During the research the ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The results showed that the coefficient of performance increased on average by about 13%, while the power consumption decreased on average by about 11%. Also, the thermodynamic characteristics of the proposed system were considerably improved [22].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the coefficient of performance increased on average by about 13%, while the power consumption decreased on average by about 11%. Also, the thermodynamic characteristics of the proposed system were considerably improved [22].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the experimental test data, the combined effects of electronic expansion valve, scroll compressor operation and the correct experimental settings of PID controller in DC refrigerator results around 62,4 % energy saving opposed to the traditional ON-OFF controlled appliance under the same operational conditions in the same cold store. The measured daily energy consumption was 14,65 kWh of the traditional ON-OFF system and 5,5 kWh of the PID controlled system [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the model was further developed which takes into account also the types of compressors, feeder and control units used commonly in practice for energetic investigations. Further object is to validate the developed simulation model with measured data by experimental tests obtained during the previous phase of the research work [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Feedback linearization, Lyapunov stability theory, and adaptive control are some of the approaches that have been applied to the system [14].Some other control methods like model predictive control (MPC) are successfully applied in this field, but it is necessary to identify a suitable model for the system [15] and installation could be expensive. This means that an accurate dynamic model from the system is required and, considering the uncertainties, makes the problem very difficult to solve.On the other hand, conventional controllers like a proportional-integral-derivative (PID) controller, usually implemented in a feedback control scheme, are the most applied controllers in this area because of the simplicity of the control law and easy implementation in continuous-time [16][17][18]. The feedback control scheme depends heavily on feedback sensors, which have some disadvantages such as cost, reliability, and noise, which can affect the output of the system.…”
mentioning
confidence: 99%
“…On the other hand, conventional controllers like a proportional-integral-derivative (PID) controller, usually implemented in a feedback control scheme, are the most applied controllers in this area because of the simplicity of the control law and easy implementation in continuous-time [16][17][18]. The feedback control scheme depends heavily on feedback sensors, which have some disadvantages such as cost, reliability, and noise, which can affect the output of the system.…”
mentioning
confidence: 99%